Shade drives plant community changes of ground‐layer savanna vegetation: Short‐term changes under an experimental approach. (10th March 2022) - Pinheiro, Luiz Felipe Souza; Pilon, Natashi Aparecida Lima; Rossatto, Davi Rodrigo; Kolb, Rosana Marta
Abstract: Aim: Woody‐plant encroachment is a reality in many savannas worldwide, leading savannas to become replaced by forest ecosystems. As tree density and cover increase, increased shade and litter deposition may suppress the savanna's community of low‐lying plants. By using field manipulation, we tested shading and litter effects, alone and in combination, on the savanna's ground‐layer plant community. We investigated how changes in these environmental factors may affect the composition, structure, and above‐ground biomass in the plant community of a species‐rich Neotropical savanna. Location: Savanna patches in the Cerrado, southeastern Brazil. Methods: Annual surveys of the herbaceous–shrub layer in a three‐year field manipulation experiment examining shading and litter deposition. Results: Shade negatively affected all evaluated parameters, while litter addition had only minor effects. The largest losses of richness, density, and cover occurred in forbs and grasses. Increased shade resulted in a sharp decrease in the above‐ground biomass of monocots. Conclusions: Our results show that light is a strong environmental filter for the ground‐layer community. The reductions in grass cover and biomass under shade treatments likely altered ecosystem functioning. Woody encroachment can thus be considered to represent a process that can alter the structure and functioning of savannas. Management interventions should therefore be taken to prevent woody encroachment or mitigate its harmful effects on savanna biodiversity and ecosystem functioning. Abstract : Shade and litter deposition have been suggested as causes of ground‐layer species disappearance in savannas under encroachment. In an experimental approach we tested the effects of shade and litter addition on the ground‐layer species of a Cerrado in southeastern Brazil. We found shade as the major driver of the decrease in richness, cover and biomass of ground‐layer species.